The Distribution of Grievability in Whitney Terrell’s The Good Lieutenant - M Ikbal M Alosman; Raihanah M. M. (Asiatic: IIUM Journal of English Language and Literature, 2026)
This essay analyses the intrinsic worth of life and the allocation of potential suffering in Whitney Terrell’s novel The Good Lieutenant (2017). Its argument expands upon Judith Butler’s assertion that the allocation of grievability varies depending on individuals’ affinities and political circumstances. In this study, we examine two paradigms: “American Lives,” which delves into the worth and grievability of American characters, and “Local Lives,” which studies the same aspects for local Iraqi personalities. While Terrell does include some Iraqi characters and discusses particular elements of the Iraqi environment, the main focus of the novel is on the Americans and their experiences, making them the primary targets of grievance. The persistent and daring search for the missing body of Sergeant Beale highlights the increased threshold of grievability attributed to Americans, therefore strengthening the belief that their lives are intrinsically more precious than those of the local Iraqi community.